The relationship of quality perfomance appraisal experience on job satisfaction and organizational commitment / Aziza Zulaikha Mustapa Kamal - Mustapa Kamal, Aziza Zulaikha (Faculty of Business and Management, 2013)
This study tries to detennine the relationship between perfonnance appraisal experience on job satisfaction and organizational commitment in PETRONAS Floating LNG 1 (Labuan) Limited. The study was conducted among 48 respondents in PETRONAS Floating LNG 1 (Labuan) Ltd. Self administered questionnaires were used to collect data from the participants. Data for this study was collected from employees of PETRONAS Floating LNG 1 (Labuan) Ltd using SPSS 18.0. The fmding of this study revealed that there was no significant relationship between perfonnance appraisal and job satisfaction and low significant relationship between perfonnance appraisal and organizational commitment.